THE CLIMATE VARIABILITY OF THE YEAR 2019 AND THE IMPACT ON THE MAIZE PRODUCTION IN THE SOUTHERN-WESTERN DEVELOPMENT REGION OF OLTENIA, ROMANIA - Dana Maria (OPREA) CONSTANTIN; Ion MARINICĂ; Andreea Floriana MARINICĂ; Elena GRIGORE; Florina TATU; Gabriela DÎRLOMAN; Dan Vasile ARDELIAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In the current context of the global warming, knowing the impact on different economic sectors can be achieved by analyzing the climate variability in both short and long term. The agricultural production is closely linked to short-term climate variability at the year level. The main purpose of the study is to analyze the temperature and precipitation regime of the year 2019, for the Southern-Western Development Region of Oltenia, in relation to the bio-climatic requirements of the maize. The year 2019, in Romania, is the warmest year from 1900 to present, according to the National Meteorological Administration (NMA). The analysis of the thermic and precipitation resources will be performed based on the meteorological-climatic data from 15 meteorological stations belonging to the National Meteorological Administration. There will be used statistical methods and GIS techniques, complemented by using the Hellmann classification for establishing the types of the thermic and precipitation weather type of the year 2019. According to this classification, the year 2019 in the study area, was a warm and normally rainy year on average. Based on these variations of the temperature and precipitation regime, at the level of the study area, there was an average production per hectare of grain maize of 5,707 kg/ha, with 1,647 kg/ha less than in 2018, which was considered a record production year from 2000 to 2020.